The Iterative Accelerative Method of Finite Element Approximation for the System $u=∑ u_j (\frac{∂ u}{∂ x_j})+f$ (Journal of Computational Mathematics, 2021)
In this paper we use an iterative method to get an approximate solution $u^n$ and $\bar{u}^n$ which approximate the exact solution $u$ with the error estimates $\|u-u^n\|+ch\|u-u^n\|_1+\|u-\bar{u}^n\|_1≤ ch^{n+2}$.